Com Deus não se brinca: o risível no evangelho de Marcos - Santos, Paulo Sérgio Macedo dos (2023)
The central objective of this research is to answer the question: how to identify laughter and the laughable in the sacred texts of the NT. We start from the perspective that the nar-ratives of primitive Christianity have their origin in popular culture, a meeting place of dif-ferent genres and irreconcilable literary characteristics. Marcos, in inaugurating the “gos-pel” genre, points out in his narrative, dependent on popular culture, all the necessary ele-ments to tell a good story. Laughter, however, to be identified in the narratives present in the Marcan text, lacks the contributions of neurolinguistics, psychoanalysis, philosophy of history and literary criticism. This work is so concerned with building the paths that the laughable made in the history of Christian culture, as well as its diabolization in the Middle Ages, as well as how it was seen by the three main cultures that influenced the construc-tion of Christianity. In Marcos, the elements that identify him as a popular culture produc-tion are visible in the forms and elements that build the narrative. This text, impregnated with “tiredness”, with alliterations, is also full of irony and sarcasm, as an authentic prod-uct of the meeting of different universes and the union of equally different styles and gen-res. In this meeting environment, in which social barriers are transposed, literary genres are intertwined, mutually coexisting, removing artificially imposed dichotomies from meaning. Having surpassed this limit imposed by a traditional reading of sacred texts, mainly those that were canonized, escaping from the traditional interpretation that laughter is nothing more than a moral fault, this appears as a substantial element for understanding both the narratives existing in the Gospel of Marcos, as well as a formative and original element of Christianity. The solidification of Christianity as a religious standard ended up demonizing this laughter and allowing it only in mockery of the devil since the medieval idea was that Christ never laughed. This was necessary for Christianity to emerge as a dominating force and to collaborate with the idea of a Manichaean division of reality imposed by the seri-ous/smiling dichotomies; tall short; grotesque/sublime; sacred/profane, exempting literature from contact with the surrounding reality. Reality of speech, cultural and linguistic influ-ences and people. Exempting the sacred from laughter was an alternative to imposing it as a religion.(AU)